3D Whole‐heart free‐breathing qBOOST‐T2 mapping. Issue 5 (21st October 2019) - Milotta, Giorgia; Ginami, Giulia; Bustin, Aurelien; Neji, Radhouene; Prieto, Claudia; Botnar, René M.
Abstract : Purpose: To develop an accelerated motion corrected 3D whole‐heart imaging approach (qBOOST‐T2) for simultaneous high‐resolution bright‐ and black‐blood cardiac MR imaging and quantitative myocardial T2 characterization. Methods: Three undersampled interleaved balanced steady‐state free precession cardiac MR volumes were acquired with a variable density Cartesian trajectory and different magnetization preparations: (1) T2‐prepared inversion recovery (T2prep‐IR), (2) T2‐preparation, and (3) no preparation. Image navigators were acquired prior the acquisition to correct for 2D translational respiratory motion. Each 3D volume was reconstructed with a low‐rank patch‐based reconstruction. The T2prep‐IR volume provides bright‐blood anatomy visualization, the black‐blood volume is obtained by means of phase sensitive reconstruction between first and third datasets, and T2 maps are generated by matching the signal evolution to a simulated dictionary. The proposed sequence has been evaluated in simulations, phantom experiments, 11 healthy subjects and compared with 3D bright‐blood cardiac MR and standard 2D breath‐hold balanced steady‐state free precession T2 mapping. The feasibility of the proposed approach was tested on 4 patients with suspected cardiovascular disease. Results: High linear correlation (y = 1.09 × −0.83, R 2 = 0.99) was found between the proposed qBOOST‐T2 and T2 spin echo measurements in phantom experiment. Good image quality was observed in vivo with the proposed 4x undersampled qBOOST‐T2. Mean T2 values of 53.1 ± 2.1 ms and 55.8 ± 2.7 ms were measured in vivo for 2D balanced steady‐state free precession T2 mapping and qBOOST‐T2, respectively, with linear correlation of y = 1.02x+1.46 (R 2 = 0.61) and T2 bias = 2.7 ms. Conclusion: The proposed qBOOST‐T2 sequence allows the acquisition of 3D high‐resolution co‐registered bright‐ and black‐blood volumes and T2 maps in a single scan of 11 min, showing promising results in terms of T2 quantification.